The effects of propofol and midazolam on the cardiotoxicity of bupivacaine in rabbits [Tavsanlarda propofol ve midazolamm bupivakain kardiyotoksisitesi uzerine etkileri] - (:unkn) unknown (My University, 1999)
This study was designed to evaluate the effects of propofol and midazolam which are widely used as hypnotic agents for sedation during regional anaesthesia on the cardiotoxicity of bupivacaine in 16 male rabbits. After induction with 5 % sevoflurane in oxygen and endotracheal intubation, venous and arterial cannulations were made and administration of sevofluran was stopped. The rabbits were awaken and randomly assigned into two groups (n=8). After 5 min of administration of 0.06 mg/kg midazolam IV in group I and immediately administration of 1.5 mg/kg propofol IV in group II, 2 mg/kg/min 0.5% bupivacaine infusion was started. When the cardiotoxic effects of bupivacaine was observed on ECG, the bupivacaine infusion was stopped and the rabbits were resusciated. The cardiotoxic effects of bupivacaine was developed significantly later and with higher doses of bupivacaine in group I (p<0.05). There was no difference in duration of resuscitation and doses of pharmacologic agents used between the groups (p>0.05). We concluded that midazolam should be preferred for sedation during regional anaesthesia with bupivacaine.
Keywords: Bupivacaine; Cardiac toxicity; Midazolam; Propofol